KONTROVERSI PENAFSIRAN “SESUATU YANG ILAHI MUNCUL DARI DALAM BUMI”:KAJIAN HERMENEUTIK BERDASARKAN 1 SAMUEL 28:13 - Aska Aprilano Pattinaja; Refamati Gulo (Manna Rafflesia, 2026)
The interpretation of the phrase “a divine being coming up out of the earth” has long been a subject of debate among biblical scholars, particularly due to the use of the term ’ĕ·lō·hîm in the sense of “divine.” The diversity of interpretations has often obscured the original meaning of this phrase. This study aims to examine and provide a clear and comprehensive interpretation of the phrase. Employing a hermeneutical approach through literature study, this research identifies two key findings: first, from a historical-cultural perspective, the term ’ĕ·lō·hîm in this context does not refer to the LORD (YHWH), but can also denote other divine or supernatural beings, including deities or objects of worship; second, within the biblical framework, anything associated with the LORD is not depicted as emerging from the earth, but rather from above (heaven), symbolizing the divine realm.The novelty of this study lies in addressing the interpretive gap concerning the meaning of “the divine” in 1 Samuel 28:13. The findings are expected to contribute to the development of biblical studies, particularly in clarifying and evaluating various interpretations of this narrative.